STRATEGI PENDAMPING LEMBAGA HIDAYATULLAH DALAM PEMBINAAN KETAHANAN MENTAL MUALLAF DI DESA PAYE MUNJE KECAMATAN LAWE ALAS KABUPATEN ACEH TENGGARA - Rahma Danti; Ismiati; Reza Muttaqin (STAI Nusantara Kota Banda Aceh, 2026)
This research is motivated by the phenomenon of psychological shock and social exclusion experienced by converts (muallaf) in Paye Munje Village post-conversion, including family rejection and expulsion. These conditions trigger emotional wounds, economic crises, and the loss of primary support systems. This study aims to analyze e assistance strategies of the Hidayatullah Institution in strengthening the mental resilience of converts through a qualitative approach with a case study method. The data collection techniques used in this study are observation, interviews, and documentation. The results indicate that the institution implements a systematization of dakwah that integrates spiritual, social, and material dimensions through three main strategies. First, the protection of administrative rights to ensure legal certainty for converts in order to provide a sense of security from the threat of social exclusion. Second, strengthening mental resilience through gradual religious guidance and adaptive personal counseling to restore psychological conditions and build the self-confidence of converts. Third, direct assistance through the placement of preachers in border areas combined with economic and educational assistance. The synergy of these three strategies is effective in alleviating the living burdens of converts, so that they are able to achieve mental stability and stronger faith amid extreme environmental challenges.